Production potential and water productivity of basmati rice (Oryza sativa)–wheat (Triticum aestivum) sequence as influenced by irrigation termination of basmati rice and irrigation scheduling of succeeding wheat - BRAR, A S; MAHAL, S S; BUTTAR, G S; DEOL, J S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted to find out the optimum time for termination of irrigation to basmati rice (Oryzasativa L.) and irrigation scheduling of wheat (Triticum aestivum L. emend Fiori & Paol) sown after basmati rice inresidual moisture without pre-sowing irrigation, during 2005–06 and 2006–07. The experiment was laid out in split plotdesign with three cut-off time of last irrigation in basmati rice (21, 28 and 35 days after flowering) in main plot andcombinations of first (14, 21 and 28 days after sowing) and subsequent irrigation schedules (1.25, 1.00 and 0.75 IW:CPE)to succeeding wheat. Cut off timings of last irrigation in basmati rice at 28 and 35 days after flowering (DAF), while beingat par with each other produced significantly higher yield and yield attributes of basmati rice and succeeding wheat thanat 21 DAF. In wheat, application of first irrigation at 14 and 21 days after sowing (DAS) while being mutually at par,recorded significantly higher yield and water-use efficiency than 28 DAS. Subsequent irrigation schedules of 1.25 and 1.0IW:CPE produced significantly higher yield of wheat than 0.75 IW:CPE schedule. Total productivity of basmati ricewheatsequence was significantly higher under 35 DAF cut off time of last irrigation to basmati rice than 28 and 21 DAF,however, both 28 and 35 DAF treatments reported almost equal water productivity with 57.4 and 60.2g more wheat grainwith each cubic metre of water than 21 DAF, respectively.